2013
DOI: 10.7251/agren1304487j
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Chemical Weed Control in Potato (Solanum tuberosum L.)

Abstract: In this paper the results of efficiency of combined application of six herbicides in weed control in potato were presented. The study was done during 2007 and 2008 in Kolašin, on acid brown soil, at an altitude of about 900 m. In the experiment the following herbicides were examined: S-metalachlor, Bentazone, Acetohlor, Flurochloridone, Metribuzin and Dimetenamid-P. The study was conducted in the Kennebec variety crop. All applied herbicides had satisfactory effect in decreasing number and biomass of weeds. As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 1 publication
1
3
0
Order By: Relevance
“…The new premix herbicide Flomex recorded a higher and a significant tuber yield than metribuzin. These results agree with the previous work of Jovović et al [54], who pointed out that acetochlor recorded a higher yield than metribuzin. Moreover, Deshi et al [55] observed that combinations of herbicides recorded significantly higher tuber yield than the herbicide alone, and also higher than the control plots.…”
Section: Tuber Yield and Qualitysupporting
confidence: 93%
“…The new premix herbicide Flomex recorded a higher and a significant tuber yield than metribuzin. These results agree with the previous work of Jovović et al [54], who pointed out that acetochlor recorded a higher yield than metribuzin. Moreover, Deshi et al [55] observed that combinations of herbicides recorded significantly higher tuber yield than the herbicide alone, and also higher than the control plots.…”
Section: Tuber Yield and Qualitysupporting
confidence: 93%
“…Moreover, this treatment in combination with harrowing was performed once before emergence. Herbicide and biostimulants were applied to the remaining objects weeded mechanically and chemically (2)(3)(4)(5). Before potato emergence, double harrowing was performed, and immediately after the second one, about 7 days before plant emergence (phase BBCH 00-08), Avatar 293 ZC herbicide was applied (clomazone and metribuzine are active substances of the preparation) at a dose of 1.5 dm 3 •ha −1 .…”
Section: Experimental and Agronomic Managementmentioning
confidence: 99%
“…In Poland, it is an important food crop, and the annual consumption of unprocessed (fresh) potatoes and processed potatoes in the 2020/2021 season was 85 kg per capita [3]. The potato yield is determined by many factors, such as soil and climatic conditions, the choice of variety and a complex of agrotechnical treatments, including careful and well-chosen plantation care [4][5][6][7]. Weeds are one of the main factors limiting the potato yields.…”
Section: Introductionmentioning
confidence: 99%
“…For the proper selection of herbicides, one of the most important prerequisites is knowledge of the weed flora in a given vineyard, because the selection of preparations for their control is made based on the weed species present. Only in this way is it possible to make a correct choice of the type and amount of herbicide, the method and time of application, which will enable the achievement of maximum effects in controlling weeds and elimination of possible negative consequences to the greatest extent for the cultivated plant, the environment, domestic animals and humans (Jovović et al, 2013).…”
Section: Introductionmentioning
confidence: 99%